Combination of violet light irradiation and collagenase treatments in a rabbit model of keratoconus - Kobashi, Hidenaga; Yano, Takashi; Tsubota, Kazuo (Frontiers in Medicine, 2023)
Purpose We evaluated the use of collagenase treatment to generate a rabbit model of keratoconus and the impact of violet light (VL) irradiation on the disease model in six Japanese White rabbits. Methods After epithelial debridement, the collagenase group was treated with a collagenase type II solution for 30 min; the control group was treated with a solution without collagenase. Three rabbits also underwent VL irradiation (375 nm, irradiance 310 μW/cm2) for 3 h daily for 7 days after topical collagenase application. Slit-lamp microscopy results, steep keratometry (Ks), corneal astigmatism, central corneal thickness, and axial length were examined before and after the procedure. The corneas were obtained on day 7 for biomechanical evaluation. Results A significant increase in Ks and corneal astigmatism was observed in the collagenase and VL irradiation groups compared with the control group on day 7. No significant difference was found in the change in corneal thickness between the groups. The elastic modulus at 3, 5, and 10% strain was significantly lower in the collagenase group than in the control group. There was no significant difference in the elastic modulus at any level of strain between the collagenase and VL irradiation groups. The average axial length at day 7 was significantly longer in the collagenase and VL irradiation groups than in the control group. Collagenase treatment induced a model of keratoconus by steepening the keratometric and astigmatic values. There was no significant difference in the observed elastic behavior of normal and ectatic corneas under physiologically relevant stress levels. Conclusion VL irradiation did not cause regression of corneal steepening in a collagenase-induced model during short-term observation.